Agent-based Modelling of vMEMEs: A Preliminary Apprasial - Srbljinović, Armano (Array, 2008)
Abstract The paper brings forth a concise review of agent-based modelling methodology with an appraisal of its application to cultural transmission, here seen as the dynamic process of value-MEME (vMEME) systems' transformation. Basic characteristics of the vMEME systems and the agent-based modelling methodology are presented. Opportunities of applying agent-based modelling techniques to vMEME systems are considered and the potential benefits of such an approach are preliminarily assessed. Major constituent elements of an agent-based simulation model of vMEME systems are discussed. The model's usage is envisioned to improve understanding of evolution, interaction and transformation of human values systems. A particularly interesting application may concern the values systems conducive to the development of a knowledge society.